Karakterisasi Genetik Kambing Gembrong dari Karangasem Bali Menggunakan DNA Mikrosatelit - Puja, I Ketut; Sulabda, I Nyoman (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
The present study was undertaken with primary objective to characterize of Gembrong goat breeds. It is essential to characterize the germplasm for intragenetic variability, which will help in planning for conservation strategy as well as genetic improvement. DNA Genome was isolated from hairs. Nine microsatellite were amflified by PCR. PCR product were run on 6% bis-Acrylamide gel in automated DNA sequencer. Flourescent signals from the dye-labeled microsatellite were detecting using STRand software. The result show that all markers (INRA005, INRA063, INRA023, ILSTS19, ILSTS87, SRCRSP8, MAF65, OarFCB20, and McM547) successfully amplified in Gembrong goat microsatellite loci. The number of alleles per locus ranged from 1 (INRA005) to 4 (ILSTS87). All the microsatellites investigated were found to be highly polymorphic, except INRA063. In total, 23 alleles were observed for the 9 microsatellite loci. The allele sizes ranged from 99 bp (OarFCB20) to 240bp (SRCRSP8). The study can be extended to include large many microsatellites in different chromosome location to validate the results.